Pray local and act global? Christian religiosity in the U.S. and human rights. (9th December 2018) - Cui, Jinhua; Jo, Hoje
Abstract: This study examines the influence of Christian religion on corporate decisions related to human rights in the United States. Specifically, it examines the empirical association between a company's human rights practices and the Christian religiosity in its local community, as well as individual CEO religiosity in the United States, both of which have not been tested in prior studies. Employing a large sample from the United States, we find a congruent association between the "human rights friendly" practices of a company and the Christian religiosity of the local community. This novel finding is robust to a diverse set of tests. In addition, we find that the association between Christian religiosity in the United States and human rights is more significant in reducing human rights concerns, than it improves human rights strengths. This study interprets these results as upholding the religious morality hypothesis, namely, that companies located in areas with higher religiosity are likely to engage in more human rights‐friendly practices, and the United States. Christians consider religion as an influencing factor that encourages managers to embrace human rights. Furthermore, this study finds that individual religious managers tend toward more human rights‐friendly practices, supporting our religious manager hypothesis.